"No One Told Me About This Part": What Breastfeeding Women Want and Need to Support Their Physical Health. Issue 2 (12th April 2021) - Snyder, Kailey; Peterson, Julie; Bargstadt-Wilson, Kari
Abstract : Background: Breastfeeding women struggle to achieve recommendations of obtaining 150 minutes of moderate activity per week or more. Pelvic floor dysfunction may be hindering postpartum physical activity. However, the severity and type of dysfunction remain poorly understood. Objective: This study had the following objectives: (1) to determine the severity of symptoms of pelvic floor dysfunction among breastfeeding women, with a secondary objective (1a) to determine whether this varied on the basis of exclusive breastfeeding versus supplementation of solids foods and/or formula and (2) to determine what breastfeeding women perceive they need in a physical activity intervention and (2a) how their activity levels change from before to after pregnancy. Study Design: This was a concurrent embedded mixed-methods cross-sectional survey. Methods: A survey consisting of demographic questions, physical activity experiences, the Pelvic Floor Distress Inventory (PFDI-20), and open-ended questions was disseminated to currently breastfeeding mothers. Results: Survey findings conclude that breastfeeding women are primarily sedentary or engage in light physical activity and experience greater symptom severity related to urinary incontinence than anal or pelvic organ prolapse distress. Symptoms are not influenced by breastfeeding exclusivity. Many women are hindered from being active by time constraints associated with feeding their infant. Women would like a combination of in-person/online pelvic floor and general exercise resources. Conclusion: A large proportion of breastfeeding women are sedentary or engaging only in light activity. Furthermore, breastfeeding women report urinary incontinence symptoms and these symptoms are not influenced by breastfeeding exclusivity. Breastfeeding women desire increased education and resources to support their physical activity.